Monitored anaesthesia care (MAC) and ophthalmic surgery - Bhattarai, BK (Nepalese Journal of Ophthalmology, 2010)
The use of monitored anaesthesia care (MAC) is increasing with the discovery of newer, more effective and appropriate drugs and techniques. MAC is intended to achieve patient comfort with safety and optimal clinical outcome and is being extensively used worldwide for cataract and other ophthalmic surgeries. This article briefly reviews the conceptual basis of MAC, its use in ophthalmic surgeries, sedative-analgesic drugs commonly used during MAC in eye surgeries, monitoring during MAC in eye surgery and the role of anaesthesia practitioners during MAC. Key words: anaesthesia; cataract; eye; monitored anaesthesia care (MAC); sedation; surgery DOI: 10.3126/nepjoph.v1i1.3674 Nep J Oph 2009;1(1):60-65